2020
DOI: 10.1111/ecog.04988
|View full text |Cite
|
Sign up to set email alerts
|

Comparing temporal patterns in body condition of ringed seals living within their core geographic range with those living at the edge

Abstract: Ecological theory suggests that demographic responses by populations to environmental change vary depending on whether individuals inhabit central or peripheral regions within the species' geographic range. Here, we tested this prediction by comparing a population of ringed seals Pusa hispida located at high latitudes as part of their core range (core) with a population located at the southern extremity of their range (peripheral). First, we compared the two regions' environmental trends in timing of sea-ice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 122 publications
(171 reference statements)
1
14
0
Order By: Relevance
“…We identified that indicators of recruitment were higher during, or following, years with lower winter AOs (Table 6; Figure 6) consistent with previous studies that have similarly shown increased frequency of predation (Pilfold et al, 2015; Rode et al, 2018), increased proportions of ringed seal in adult female and juvenile diets (McKinney et al, 2017), and lower hair cortisol levels (Bechshoft et al, 2013) during years with lower winter AOs. Lower winter AOs have also been associated with increased abundance and productivity of ringed seals (Ferguson et al, 2020; Nguyen et al, 2017) and may represent aspects of sea ice conditions important to polar bear foraging, such as sea ice thickness (Park et al, 2018; Rigor et al, 2002), that are not reflected in satellite data of sea ice area and concentration. In Svalbard, body mass of adult male and female polar bears, cubs per female per year, and the proportion of females accompanied by cubs were similarly negatively correlated with the AO (Derocher, 2005) suggestive that the winter AO may be an important factor influencing cub production, survival, or both across Arctic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified that indicators of recruitment were higher during, or following, years with lower winter AOs (Table 6; Figure 6) consistent with previous studies that have similarly shown increased frequency of predation (Pilfold et al, 2015; Rode et al, 2018), increased proportions of ringed seal in adult female and juvenile diets (McKinney et al, 2017), and lower hair cortisol levels (Bechshoft et al, 2013) during years with lower winter AOs. Lower winter AOs have also been associated with increased abundance and productivity of ringed seals (Ferguson et al, 2020; Nguyen et al, 2017) and may represent aspects of sea ice conditions important to polar bear foraging, such as sea ice thickness (Park et al, 2018; Rigor et al, 2002), that are not reflected in satellite data of sea ice area and concentration. In Svalbard, body mass of adult male and female polar bears, cubs per female per year, and the proportion of females accompanied by cubs were similarly negatively correlated with the AO (Derocher, 2005) suggestive that the winter AO may be an important factor influencing cub production, survival, or both across Arctic systems.…”
Section: Discussionmentioning
confidence: 99%
“…We also considered the potential for the winter AO to affect polar bear recruitment, body condition, diet, and feeding probability because the AO appears to capture aspects of environmental conditions important to polar bear feeding ecology that are not reflected directly in the limited sea ice and prey metrics available (i.e., Derocher, 2005;McKinney et al, 2017;Pilfold et al, 2015;Rode et al, 2018). When the winter AO index is lower, older thicker ice occurs in the central Arctic (Rigor et al, 2002) and lower AOs have been associated with higher densities and body condition in ringed seals (Ferguson et al, 2005(Ferguson et al, , 2020. Although the seasonal extent of sea ice can be quantified via satellite data, there are likely other features of sea ice (e.g., the availability of leads and thickness) that affect polar bear predation rates, some or all of which may be indicated by the winter AO.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the decreasing blubber thickness of ringed seals from the CAA since 1990 (Harwood et al, 2020), and coincides with our finding of a decreasing trophic position over time. Ferguson et al (2020) forecasted reproductive difficulties and higher mortality for ringed seals in the low Arctic, which showed greater seasonal fluctuation in body condition compared to ringed seals from the high-Arctic. This could be amplified by the longer exposure of ringed seals to the less lipid-rich food web in the mid-Arctic compared to ringed seals in the CAA.…”
Section: Temporal Trend In Food Web Structurementioning
confidence: 98%
“…It is likely that such changes in zooplankton dynamics also occurred at lower latitudes. The CAA is typically more ice-covered throughout the year and has exhibited stronger environmental change compared to Southern Baffin Bay (Figure 2), and Hudson Bay since 1990 (Ferguson et al, 2020). The consistency in Cor-δ 15 N trophic values of ringed seals from Baffin Island in the last 25 years suggests that the food web structure in Southern Baffin Bay has remained stable since the 1990s.…”
Section: Temporal Trend In Food Web Structurementioning
confidence: 99%
See 1 more Smart Citation